2012
DOI: 10.1109/tap.2012.2186245
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Simulation and Measurements of CBS Antennas Loaded With Non-Uniformly Biased Ferrite Material

Abstract: When ferrite materials are used in antenna designs, they introduce some interesting and unique performance characteristics. One of the attractive features, for example, is the ability to reconfigure the center frequency of the antenna. In addition, ferrite materials also introduce a number of challenges in the modeling and simulation of such antennas.In order for the ferrite material to be useful in an antenna design, it usually is subjected to an external magnetic field. This field induces the internal magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Such an electric field distribution, with weak electric fields both at the aperture and corners, leads to a low gain and impedance mismatch. This resonant frequency is much higher than that of the geometry investigated in [1]. To maintain the resonant frequency low, larger currents were applied to the coil One of the solutions to overcome the reduction in the resonant frequency sensitivity is to introduce more ferrite material on both sides of the cavity, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an electric field distribution, with weak electric fields both at the aperture and corners, leads to a low gain and impedance mismatch. This resonant frequency is much higher than that of the geometry investigated in [1]. To maintain the resonant frequency low, larger currents were applied to the coil One of the solutions to overcome the reduction in the resonant frequency sensitivity is to introduce more ferrite material on both sides of the cavity, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The first step is to find out the reasons for the low gain and poor impedance match of the ferrite-loaded CBS antenna which was reported in [1]. To overcome these drawbacks, other configurations of ferrite material will be suggested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1], the nonuniform applied magnetic field and nonuniform magnetic field internal to the ferrite specimen was modeled. In [2], some design guidelines to enhance the gain, impedance match and tunable bandwidth of a rectangular cross-section cavity was developed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, low loss ferrite having large l r and e r is indispensable [8,9]. A dc bias magnetic field was applied to a ferrite antenna to lower magnetic tangent loss, thereby improving antenna gain [10][11][12][13][14][15][16][17]. It was observed that antenna gain was improved with the dc magnetic field.…”
mentioning
confidence: 99%